Asuhan Gizi pada Pasien Diabetes Melitus, Hipertensi dan Penyakit Jantung Koroner NSTEMI : Studi Kasus - Maulidina Maiyarani Amroe (Pusat riset dan Inovasi Nasional, 2026)
Diabetes mellitus accompanied by hypertension and coronary heart disease requirescomprehensive nutritional management to improve clinical conditions and prevent further complications.This study aimed to describe the implementation of standardized nutritional care for a patient with diabetesmellitus, hypertension, and coronary heart disease with Non-ST Elevation Myocardial Infarction(NSTEMI) during hospitalization at a private hospital in Surabaya. The method used was a case studyapplying the standardized Nutrition Care Process, including assessment, diagnosis, intervention,monitoring, and evaluation. The assessment results showed that the patient experienced hyperglycemiawith a random blood glucose level of 495 mg/dL and HbA1c of 12.5%, blood pressure of 170/95 mmHg,and required fluid restriction due to cardiovascular conditions. The nutritional diagnoses establishedincluded the need to reduce simple carbohydrate intake, sodium and cholesterol restriction, fluidrestriction, and readiness for lifestyle modification. The nutritional intervention consisted of a diabetesmellitus diet, Dietary Approaches to Stop Hypertension (DASH), and a cardiac diet accompanied bynutrition education using leaflet media. Monitoring over three days showed a gradual improvement in foodintake, sodium and cholesterol intake remained within recommended limits, and clinical improvement wasobserved, particularly in decreased blood pressure and blood glucose levels toward normal ranges. It canbe concluded that the implementation of standardized nutritional care in patients with diabetes mellitus,hypertension, and NSTEMI coronary heart disease helped improve dietary intake and supported thestabilization of the patient’s clinical condition during hospitalization.